2020
DOI: 10.1111/iej.13353
|View full text |Cite
|
Sign up to set email alerts
|

MTT versus other cell viability assays to evaluate the biocompatibility of root canal filling materials: a systematic review

Abstract: Objectives This systematic review aimed to compare the cytotoxicity of root canal filling materials (RCFMs) assessed using tetrazolium salt‐based tests (TSBT), including the 3‐(4,5‐dimethylthiazol‐2‐yl)‐2,5‐diphenyl tetrazolium bromide (MTT) assay, with those obtained using other cell viability assays. Methods A search was performed on PubMed, Scopus, Web of Science and OpenGrey up to March 2019, followed by a manual search. According to the Participants, Exposure, Comparator and Outcomes (PECO) criteria, in v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0
2

Year Published

2021
2021
2025
2025

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(23 citation statements)
references
References 64 publications
1
20
0
2
Order By: Relevance
“…Considering that the present study proposed to simulate the clinical situation of VPT, the evaluation of these materials was carried out using extracts of the materials (1:1–1:16) that mimic the contact of the materials with the pulp tissue, as the concentration decreases with the elimination of leachable components by the extracellular fluid (Mestieri et al, 2015). The analysis of cell viability at 24 h using MTT is a classical assay that is widely used to evaluate the cytotoxic effects of new materials (Ghilotti et al, 2020; López‐García et al, 2019; Mestieri et al, 2015), and it is considered the gold standard (Pintor et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Considering that the present study proposed to simulate the clinical situation of VPT, the evaluation of these materials was carried out using extracts of the materials (1:1–1:16) that mimic the contact of the materials with the pulp tissue, as the concentration decreases with the elimination of leachable components by the extracellular fluid (Mestieri et al, 2015). The analysis of cell viability at 24 h using MTT is a classical assay that is widely used to evaluate the cytotoxic effects of new materials (Ghilotti et al, 2020; López‐García et al, 2019; Mestieri et al, 2015), and it is considered the gold standard (Pintor et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…When the RO concentration was increased to 4,000 mg/L, clear effects were observed and the viability of CCD-966SK and HEMn cells was decreased to 82.5% ± 1.8% and 85.2% ± 1.6%, respectively. Although cell viability was affected by RO concentrations 2,000-4,000 mg/L compared with the control, RO was not toxic to the cells because cell viability remained ≥80% [34].…”
Section: Cytotoxic Effectsmentioning
confidence: 86%
“…MTT has been shown as a reliable method for in-vitro cytotoxicity evaluation of materials used in endodontics [ 17 ]. Previous studies indicated that MTA Angelus has high biocompatibility [ 16 , 18 , 19 ].…”
Section: Discussionmentioning
confidence: 99%